(3y-5w)(7y+6w-1)=

Simple and best practice solution for (3y-5w)(7y+6w-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3y-5w)(7y+6w-1)= equation:


Simplifying
(3y + -5w)(7y + 6w + -1) = 0

Reorder the terms:
(-5w + 3y)(7y + 6w + -1) = 0

Reorder the terms:
(-5w + 3y)(-1 + 6w + 7y) = 0

Multiply (-5w + 3y) * (-1 + 6w + 7y)
(-5w * (-1 + 6w + 7y) + 3y * (-1 + 6w + 7y)) = 0
((-1 * -5w + 6w * -5w + 7y * -5w) + 3y * (-1 + 6w + 7y)) = 0

Reorder the terms:
((5w + -35wy + -30w2) + 3y * (-1 + 6w + 7y)) = 0
((5w + -35wy + -30w2) + 3y * (-1 + 6w + 7y)) = 0
(5w + -35wy + -30w2 + (-1 * 3y + 6w * 3y + 7y * 3y)) = 0

Reorder the terms:
(5w + -35wy + -30w2 + (18wy + -3y + 21y2)) = 0
(5w + -35wy + -30w2 + (18wy + -3y + 21y2)) = 0

Reorder the terms:
(5w + -35wy + 18wy + -30w2 + -3y + 21y2) = 0

Combine like terms: -35wy + 18wy = -17wy
(5w + -17wy + -30w2 + -3y + 21y2) = 0

Solving
5w + -17wy + -30w2 + -3y + 21y2 = 0

Solving for variable 'w'.

The solution to this equation could not be determined.

See similar equations:

| y^2-4y-5=x | | 9+4x=2x+33 | | W^3=-5 | | 8(-3x)-5x=-87 | | -4=2(-3x) | | 4(x-7)n=2 | | 5(r-4)r=9 | | 6x-6-5x+1=-2+5 | | 4r+3w+2p=39 | | 5x+2=26+x | | 14x-2-13x-2=-6 | | W^3=(1/343) | | 4x+3y+2z=39 | | 3-6=x-2+9 | | 3-6=x-2+6 | | 3-5=y-7 | | a+4=-10 | | 1/4.16 | | 4/13y=12 | | 120x^2+84x-144=0 | | -3/10x=18 | | 3.4/y=2.5/5.2 | | (X-4)(3x-6)=9 | | -6/13y=-18 | | 12/60=-15/y | | x^2+y^2-4x-4y-26=0 | | 4x/6=9/8 | | X/6-9=120 | | X+6=7x+12 | | 0.2+x=0.8 | | -4.2/29.4=-6/n | | sinx=1/cos10x |

Equations solver categories